(untitled) (Research, Society and Development, 2020)
The spittlebug Mahanarva fimbriolata is one of the main pests in sugar cane and has caused serious damage. The aim of this study was to evaluate the pathogenicity of different bioinsecticides based on the entomopathogenic fungus Metarhizium anisopliae on spittlebug nymphs. Five nymphs of the 4th instar were placed in Petri dishes containing sanitized cane leaf. Bioinsecticides Metarriz® Metarril®; M. anisopliae JCO®; Metiê® and Gr-Inn CE® were applied on nymphs and sugarcane leafs with pressure 15 lbs.in-² and kept at 25±1 ºC, RH 70±10% and 12h photofase. The accumulated mortality and corrected mortality were calculated by Abbott´s formula for the 3rd day after spraying and submitted to analysis of variance by the F test, Tukey P ≤ 0.05, and LT50 (lethal time). Metarril®, Metarriz® and Gr-Inn CE® Bioinsecticides showed 91.7, 87.5 and 84.2% of corrected mortality and 93.3, 90.0 and 86.7% of accumulated mortality. The bioinsecticide Metarriz® presented the highest mortality with shortest LT50 (0.9 days) on the first day, on the second day Metarriz® and Metarril® obtained mortalities of 86.7 and 80%, respectively. On the 3rd, 4th and 5th day the bioinsecticides presented pathogenicity above 70%.